Exploration of the COVID-19 mental health implications in elite disabled athletes - Amos, B.; Tibbert, S. J. (Journal of Sports Sciences, 2024)
The COVID-19 pandemic influenced the way individuals conducted their lives, with consequences relating to mental health deterioration. Whilst researchers explored this outcome in the general population and athletic populations, less focus was on athletes with disabilities. The aim of this study was to investigate how the pandemic influenced the mental health of elite para-athletes in the United Kingdom. Nine elite-level athletes with disabilities participated in semi-structured interviews. Three broad themes were interpreted from the data using reflexive thematic analysis, two themes reflected the negative impact of COVID-19 on mental health and one theme reflected positive outcomes of the pandemic. Athletes explained that losing face-to-face interactions and delays in major sporting events were significant factors in their mental health decline. This population group reported different challenges to able-bodied communities. Differences included increased susceptibility to contract the virus, difficulties in communication where face masks and online interactions became necessary and perceptions of vulnerability relating to shielding protocols. Finally, positive outcomes related to the additional time to recover, to prepare for major events and time to reassess their values. Exploring experiences of a pandemic on this population group warrants further exploration to enhance the effectiveness of mental health support services in para-sporting organisations.